Стратегічні напрями політики енергоефективності в Україні - Ліщук, Віра Іванівна; Ліщук, Михайло Євгенович; Московчук, Алла Тимофіївна; Lishchuk, Vira I.; Moskovchuk, Alla T.; Lishchuk, Mykhailo Ye. (Східноєвропейський національний університет ім. Лесі Українки, 2016)
У статті здійснено порівняльний аналіз енергоефективності країн Світу і джерел формування енергетичного продукту. Простежено тенденції у структурі енергетичних ресурсів України. Узагальнено основні стратегічні завдання політики створення енергоефективного суспільства в Україні, виявлено недоліки та запропоновано напрями удосконалення. The article shows the main trends in world energy markets, which determine energy policy, summarizes the scope and strategic objectives. A comparative analysis of energy efficiency, availability of energy resource in region and individual countries was conducted. The structure and dynamics of the formation of energy sources in Ukraine, the structure of their use, import dependence were evaluated. Major activities that are included into the strategy energy efficiency were estimated. Pointed their strengths and weaknesses. The basic ways of improvement of the strategic objectives in terms of complex energy policy formation. It should be part of country Socio-economic Development Strategy and determine the basic guidelines for regional programs of energy efficiency, including national and regional energy efficiency indicators, effective mechanisms of its stimulation and adapt to the economic and political situation in the country.
Strategic issues at energy efficiency policy of Ukraine
Keywords: енергоефективність; енергозаощадження; енергетичні ресурси; енергетичний продукт; чистий імпорт; енергетична стратегія; energy efficiency; energy conservation; energy resources; energy product; net imports; energy strategy